Microcontroller design for security system: implementation of a microcontroller based on STM32F103 microchip. (20th September 2019) - Marie, Tabi Fouda Bernard; Han, Dezhe; An, Bowen
In the monitoring system, the server can crash at any time; therefore a low-cost performant microcontroller is implemented to enable the server to reset after crashing while protecting its data core, and then be able to display in real time the information saved during the crash. This paper encompasses a complete successful designed and tested microcontroller based on STM32F103C8T6 microchip. The design of the microcontroller through a printed circuit board (PCB) prototype, peripherals and chips was assembled to reset the server from the relay chip. The connection and data communication between the microcontroller and the server are via universal serial bus (USB) and J-link connection. The design is also using the AES256encryption algorithm to protect the data of the system. The simulation results show that after the server crashes, it can easily restart and run, avoiding hassles with insurance of protecting the data core of the system.